ANALISIS PENGGUNAAN (DIKSI) PILIHAN KATA OLEH PEJABAT LEGISLATIF DAN TOKOH PARTAI TINGKAT PROVINSI DALAM MEDIA SOSIAL FACEBOOK - Sari, Roza Permata; Juita, Novia (Jurnal Bahasa dan Sastra, 2019)
The purpose of this study was to describe the forms of errors in use (diction) of the choice of words by provincial legislative and party leaders in West Sumatra on social media. This study used descriptive qualitative method. The data source in this study is utterances written by legislative officials and party leaders on Facebook. The results showed 199 data / utterances were careful, in the use of word choice in terms of inaccuracy, inaccuracy, and discrepancies, found 13 speeches that did not follow the use of word choice in terms of discrepancies, 3 utterances that did not follow the use of word choice in terms of inaccuracies, and 2 utterances that do not follow the use of word choices in terms of non-conformityKeyword: word choice, legislative officers, facebook